2015
DOI: 10.3389/fpls.2015.00846
|View full text |Cite
|
Sign up to set email alerts
|

Cytomixis doesn’t induce obvious changes in chromatin modifications and programmed cell death in tobacco male meiocytes

Abstract: Cytomixis is a poorly studied process of nuclear migration between plant cells. It is so far unknown what drives cytomixis and what is the functional state of the chromatin migrating between cells. Using immunostaining, we have analyzed the distribution of posttranslational histone modifications (methylation, acetylation, and phosphorylation) that reflect the functional state of chromatin in the tobacco microsporocytes involved in cytomixis. We demonstrate that the chromatin in the cytomictic cells does not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Due to slow-paced progression during prophase I, for instance, assembly/disassembly of the bouquet and the SC or formation and dissolution of interlocks could be studied in detail. In numerous plant species, primarily during male prophase I, cytomixis occurs, i.e., migration of whole nuclei, chromosomes and/or chromatin between plant cells through intercellular channels (cytomictic channels) resulting in the formation of unreduced, polyploid, aneuploid or sterile pollen ( Mursalimov et al, 2015 ; Mursalimov and Deineko, 2017 ). How cytomixis is regulated or interconnected to meiotic progression is unclear.…”
Section: Novel Approaches Exploiting Non-model Plantsmentioning
confidence: 99%
“…Due to slow-paced progression during prophase I, for instance, assembly/disassembly of the bouquet and the SC or formation and dissolution of interlocks could be studied in detail. In numerous plant species, primarily during male prophase I, cytomixis occurs, i.e., migration of whole nuclei, chromosomes and/or chromatin between plant cells through intercellular channels (cytomictic channels) resulting in the formation of unreduced, polyploid, aneuploid or sterile pollen ( Mursalimov et al, 2015 ; Mursalimov and Deineko, 2017 ). How cytomixis is regulated or interconnected to meiotic progression is unclear.…”
Section: Novel Approaches Exploiting Non-model Plantsmentioning
confidence: 99%
“…Some scientists suggest that the chromosomal polymorphisms of microsporocytes and pollen grains, as well as a large variety of natural polyploid cytotypes in many plant species confirm the involvement of migrant chromatin in the karyotype restructuring (Zheng et al, 1987;Zhou, 2003;Malallah and Attia, 2003;Lattoo et al, 2006;Ghaffari, 2006;Lattoo et al. 2006;Negron-Ortiz, 2007;Kumar and Singhal, 2008;Pierre e de and Sousa, 2011;Singhal et al, 2011a,b;Rana et al, 2013;Mandal et al, 2013;Mursalimov et al, 2013Mursalimov et al, , 2015bReis et al, 2015).…”
Section: Peculiarities Of Nuclear Interactions and Nuclear Translocationmentioning
confidence: 99%
“…Using electron and fluorescence microscopy, transgenic plants expressing H2B‐CFP as well as FISH‐method for marking telomeric repeats of chromosomes, it was shown that the nuclear envelope and chromatin remain intact in cytomictic migrations (Wang et al, ; Liu et al, ; Mursalimov and Deineko, ; Mursalimov et al, ,). In these experiments the micronuclei and migrating chromatin emitted multiple telomeric signals, which were either localized in clusters or dispersed, depending upon the meiosis stage (Mursalimov et al, ).…”
Section: Peculiarities Of Nuclear Interactions and Nuclear Translocationmentioning
confidence: 99%
“…8,[13][14][15][16] On transgenic tobacco lines showed that cytomictic chromatin retains not only its physical, but functional properties as well. [17][18][19] The chromosomal polymorphism of microsporocytes and pollen grains, the existence of a large variety of natural polyploid cytotypes in many cytomictic species as well as fact that cytomixis is attributed to male generative sphere and "male-driven" evolution allow us to consider cytomixis as one of the mechanisms to increase genetic diversity and speciation in plants. 2,[8][9][10][11][12][16][17][18][20][21][22] The wide occurrence of cytomixis in terrestrial plants testifies its being involved in the important genomic reorganization processes, which allow its carriers to be maintained due to natural selection process.…”
Section: Introductionmentioning
confidence: 99%